Electrospun Scaffolds as Antimicrobial Herbal Extract Delivery Vehicles for Wound Healing - Caglar Ersanli; Chrysoula (Chrysa) Voidarou; Athina Tzora; Konstantina Fotou; Dimitrios I. Zeugolis; Ioannis Skoufos (Journal of Functional Biomaterials, 2023)
Herbal extracts have been used in traditional remedies since the earliest myths. They have excellent antimicrobial, anti-inflammatory, and antioxidant activities owing to various bioactive components in their structure. However, due to their inability to reach a target and low biostability, their use with a delivery vehicle has come into prominence. For this purpose, electrospun nanofibrous scaffolds have been widely preferred for the delivery and release of antimicrobial herbal extracts due to the flexibility and operational versatility of the electrospinning technique. Herein, we briefly reviewed the electrospun nanofibrous scaffolds as delivery systems for herbal extracts with a particular focus on the preclinical studies for wound-healing applications that have been published in the last five years. We also discussed the indirect effects of herbal extracts on wound healing by altering the characteristics of electrospun mats.